Why Can't I Trade? Exchange Discretion in Calling Halts*,† - Marshall, Nathan T.; Rogers, Jonathan L.; Zechman, Sarah L.C. (Contemporary Accounting Research, 2023)
ABSTRACT Stock exchanges are important intermediaries in how firm information enters price. Trading halts are a key tool, often exercised at the exchanges' discretion, to prevent extraordinary price volatility when new information arrives. We investigate how exchanges use discretion and whether the discretion alters the effectiveness of the halts. We provide evidence consistent with halts reflecting the preferences of listed firms rather than the stated exchange objectives (i.e., minimizing excess volatility and off‐equilibrium trades). Furthermore, when exchanges exercise more discretion (unexplained by firm and information characteristics), the halts are less effective. Specifically, halts with more discretion are less likely to resume trading with efficient prices and are more likely to have been called unnecessarily (i.e., little to no price movement during the halt). These findings are consistent with exchanges using halts to cater to listed firms rather than to meet exchange objectives such as minimizing excess volatility or avoiding trades at off‐equilibrium prices.